Top-Funded Digital Health Companies And Their Impact On High-Burden, High-Cost Conditions - Safavi, Kyan; Mathews, Simon C.; Bates, David W.; Dorsey, E. Ray; Cohen, Adam B. (Health Affairs, 2019)
Digital health companies hold promise to address major health care challenges, though little has been published on their impact. We identified the twenty top-funded private US-based digital health companies to analyze their products and services, related peer-reviewed evidence, and the potential for impact on patients with high-burden conditions. Data analytics (including artificial intelligence and big data) was the most common company type. Companies producing biosensors had the greatest funding. Publications were concentrated among a small number of companies. Healthy volunteers were most commonly studied. Few studies enrolled high-burden populations, and few measured their impact in terms of outcomes, cost, or access to care. These data suggest that leading digital health companies have not yet demonstrated substantial impact on disease burden or cost in the US health care system. Our findings indicate the importance of fostering an environment, with regard to policy and the consumer market, that encourages the development of evidence-based, high-impact products.